2016
DOI: 10.1002/chem.201503869
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Linear Complex Arrays of up to Eight Cuprous Centers

Abstract: Linearly arranged metal atoms that are embedded in discrete molecules have fascinated scientists across various disciplines for decades; this is attributed to their potential use in microelectronic devices on a submicroscopic scale. Luminescent oligonuclear Group 11 metal complexes are of particular interest for applications in molecular light-emitting devices. Herein, we describe the synthesis and characterization of a rare, homoleptic, and neutral linearly arranged tetranuclear Cu(I) complex that is helicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 68 publications
(134 reference statements)
1
64
0
Order By: Relevance
“…Multidentate ligands based on amidinato backbones have been frequently employed to synthesize multinuclear copper(I) complexes. The three tetracopper(I) complexes [Cu 4 {μ 4 ‐κ 4 ‐Me 2 Si(NC(Ph)N‐2,6‐ i Pr 2 C 6 H 3 ) 2 } 2 ] ( 92 ), [Cu 4 (μ 4 ‐κ 4 ‐PAA Dipp ) 2 ] (PAA=pyridylamidoamidinato) ( 93 ), and [Cu 4 {μ 4 ‐κ 4 ‐C 2 H 4 (NC(Ph)N‐2,6‐Me 2 C 6 H 3 ) 2 } 2 ] ( 94 ) supported by amidinate‐based tetradentate ligands are shown in Figure . Complexes 92 and 93 were obtained from the reactions between CuI and the sterically congested dilithiated silyl‐linked bisamidinate and PAA, respectively, whereas 94 was obtained by reacting the ethylene‐tethered bisamidine and [Cu(Mes)] 4 .…”
Section: Intramolecular Cuprophilic Interactions In Cui Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidentate ligands based on amidinato backbones have been frequently employed to synthesize multinuclear copper(I) complexes. The three tetracopper(I) complexes [Cu 4 {μ 4 ‐κ 4 ‐Me 2 Si(NC(Ph)N‐2,6‐ i Pr 2 C 6 H 3 ) 2 } 2 ] ( 92 ), [Cu 4 (μ 4 ‐κ 4 ‐PAA Dipp ) 2 ] (PAA=pyridylamidoamidinato) ( 93 ), and [Cu 4 {μ 4 ‐κ 4 ‐C 2 H 4 (NC(Ph)N‐2,6‐Me 2 C 6 H 3 ) 2 } 2 ] ( 94 ) supported by amidinate‐based tetradentate ligands are shown in Figure . Complexes 92 and 93 were obtained from the reactions between CuI and the sterically congested dilithiated silyl‐linked bisamidinate and PAA, respectively, whereas 94 was obtained by reacting the ethylene‐tethered bisamidine and [Cu(Mes)] 4 .…”
Section: Intramolecular Cuprophilic Interactions In Cui Complexesmentioning
confidence: 99%
“…To assemble more than four copper atoms in a linear array was a tough task, as evidenced by the limited examples. Based on the ethylene‐tethered tetradentate bisamidinate, Stollenz and co‐workers reported the octacopper(I) complex 105 obtained through dimerization of the tetracopper(I) complex 94 (Figure ) . The dimeric 105 only existed in the solid state and dissociated into two monomeric tetracopper(I) species 94 in solution.…”
Section: Intramolecular Cuprophilic Interactions In Cui Complexesmentioning
confidence: 99%
“…[1] Furthermore,o ne-dimensional (1D) assemblies of transition-metal complexes ("molecular wires") are of high interest for molecular microelectronics applications and studying processes of electron transfer in metal chains. However,t ovary the metal chain length, new ligand scaffolds usually need to be synthesized in elaborate processes.C urrently,e xamples of well-defined Cu I chains containing three, [10] four, [9a, 11] or more [12] Cu atoms are still rare.Thea bove methods describe bottom-up syntheses with metal precursors and ligands.T ot he best of our knowledge, examples of dynamic interconversions between linear chains of different nuclearities have not been reported, although examples of reversible interconversions between polynuclear complexes of different geometries are known (e.g., metal clusters involving non-linear metal assemblies). [2b, 3] In addition, Cu I "wires" and clusters of various nuclearities have been shown to have interesting photophysical properties that render them suitable for optoelectronic applications.…”
mentioning
confidence: 99%
“…[2b, 3] In addition, Cu I "wires" and clusters of various nuclearities have been shown to have interesting photophysical properties that render them suitable for optoelectronic applications. However,t ovary the metal chain length, new ligand scaffolds usually need to be synthesized in elaborate processes.C urrently,e xamples of well-defined Cu I chains containing three, [10] four, [9a, 11] or more [12] Cu atoms are still rare. [6] Recently,t heoretical studies indicated that multicopper coordination to DNAb ase pairs may improve the conductivity of DNA-based nanowires.…”
mentioning
confidence: 99%
See 1 more Smart Citation